Representasi Makna Poster Kajian Dakwah di Instagram Anak Mesjid - Musa, Akmal (IAIN Padangsidimpuan, 2024)
Preaching in the modern era has evolved with various methods and approaches to effectively convey messages of goodness. One of these methods is applied by the Anak Mesjid da'wah community, which utilizes posters uploaded to their Instagram account as a means of spreading religious values. This study aims to analyze the meanings embedded in these posters using Roland Barthes' semiotic analysis approach. Through this method, the study examines the posters at both the denotative and connotative levels to uncover the deeper messages they convey. The research findings indicate that the messages in the posters are consistently persuasive, utilizing a combination of text and visual elements to enhance their communicative effectiveness. The strategic use of typography, color schemes, and imagery strengthens the intended da'wah messages, making them more appealing and engaging for social media users. The ability of these posters to capture attention and deliver religious teachings in a concise yet impactful manner demonstrates the potential of digital platforms as effective da'wah tools. This study provides valuable insights into how the Anak Mesjid da'wah community integrates digital media into their preaching efforts. The findings contribute to the ongoing development of contemporary da'wah strategies, ensuring their relevance in an increasingly digitalized world.